PENGARUH WORK-LIFE BALANCE IBU BEKERJA TERHADAP KESEJAHTERAAN EMOSIONAL ANAK DAN KEHARMONISAN KELUARGA DI DUSUN NGAGLIK - Umi Miza Wirdani; Adhi Kusumastuti (IKIP Siliwangi, 2026)
The main goal of this research is to understand how the work-life balance of working mothers affects the emotional well-being of children and family harmony in Ngaglik Village. The type of research used is explanatory research with a quantitative approach. The number of participants in the study was 36, and this was a complete sample. The data analysis in this research was carried out using descriptive analysis and path analysis methods. To analyze the data using the IBM SPSS Statisticsprogram for Windows. The path analysis results show that the variable Work-Life Balance for Working Mothers (X) has a significant effect on the Emotional Well-being of Children (Y1) with a significance value of 0.001 (0.001 < 0.05) and on Family Harmony (Y2) with a significance value of 0.001 (0.001 <0.05). The batter work-life balance working mothers have, the better emosional well-being of their children and the family harmony that is created.